Les agencements organisationnels des Innovations Numériques Gestionnaires (ING) contemporaines - Jean-Sébastien Vayre; Camilo de la Torre (Communication)
The modernization movement over the last ten years has led to the significant development of Digital Management Innovations (DMI) within organizations. For their promoters, these DMI are a set of management tools designed to facilitate the exploration and exploitation of data to unleash the creativity of economic actors. To better identify and understand the relationships between these innovations and the organization of work, we seek to address the following question: what are the logics of action that drive the organizational arrangements within which DMI are developed? Based on a study of three fields of investigation, we make the assumption that DMI are at the crossroads of investigative, coopetitive, and authoritarian logics, which steer their deployment towards work horizons that do not always appear virtuous.